1964
DOI: 10.1002/andp.19644690502
|View full text |Cite
|
Sign up to set email alerts
|

Intensified Tunnel Effect for Complex Particles

Abstract: A quantum-mechanical problem about the penetration through the potentical barrier of two particles in mutual bound state (complex particle) is considered. The account of the internal structure of a complex particle leads to a spreading of the potential barrier which facilitates the penetration through this barrier.The Hamilbonian of the system of two particles interacting with each other by means of the potential v12(x! -x2) and moving in the external field vl(yl) which affects t.he particle 1 (the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…This model allows one to study the limiting cases and shows that the finite size of a tunnelling system may be very important. Similar results for a pair of particles bound in an infinite potential box, while one of the particles encounters a rectangular barrier, were found in the old paper by Zakhariev and Sokolov [7], with the conclusion that the effective barrier is modified which facilitates the penetration. We show also that the electrostatic polarizability of a composite particle adiabatically approaching the Coulomb barrier increases the tunnelling probability.…”
Section: Introductionsupporting
confidence: 83%
“…This model allows one to study the limiting cases and shows that the finite size of a tunnelling system may be very important. Similar results for a pair of particles bound in an infinite potential box, while one of the particles encounters a rectangular barrier, were found in the old paper by Zakhariev and Sokolov [7], with the conclusion that the effective barrier is modified which facilitates the penetration. We show also that the electrostatic polarizability of a composite particle adiabatically approaching the Coulomb barrier increases the tunnelling probability.…”
Section: Introductionsupporting
confidence: 83%
“…We use Crank-Nicholson integration because the method is unconditionally stable and because convergence is second order in time; that is, error is proportional to ( t ) 2 . Conversely, the convergence of Euler methods is only first order in time [i.e., ∝ ( t ) 1 ], and such methods are not unconditionally stable.…”
Section: B Numerical Methodsmentioning
confidence: 99%
“…The study of the quantum tunneling of molecules, however, is a relatively new area of research, with most publications appearing since 2005. The first investigation of two particles in a bound state penetrating a potential barrier was made by Zakhariev and Sokolov [1]. The next examination of molecular tunneling did not occur until 1994, with the investigation by Saito and Kayanuma of the resonant tunneling of a pair of bound particles upon a single external barrier [2].…”
Section: Introductionmentioning
confidence: 99%
“…Another important problem is tunnelling of composite objects through barriers [5], with applications in nuclear fusion [6], induced decay of false vacuum [7], and tunnelling of Cooper pairs in superconductors and Wannier-Mott excitons in semiconductor heterostructures [8]. It had been shown that the probability of tunnelling of an object possessing an internal degree of freedom -for example, a diatomic molecule -through a barrier may greatly exceed that of a structureless object with similar properties due to appearance of quasi-bound states in the combined scattering and molecular binding potentials [5][6][7]. Furthermore, interaction of a molecule with the ex- * fumika@physics.ubc.ca † litinskaya@gmail.com ‡ unruh@physics.ubc.ca ternal potential can induce transitions between molecular states due to coupling between relative and centre of mass (CM) coordinate degrees of freedom [9,10].…”
Section: Introductionmentioning
confidence: 99%